Answer:
Answer: {x = -6 , y = -2
Explanation:
Solve the following system:
{2 x - 18 y = 24 | (equation 1)
9 y - 5 x = 12 | (equation 2)
Swap equation 1 with equation 2:
{-(5 x) + 9 y = 12 | (equation 1)
2 x - 18 y = 24 | (equation 2)
Add 2/5 × (equation 1) to equation 2:
{-(5 x) + 9 y = 12 | (equation 1)
0 x - (72 y)/5 = 144/5 | (equation 2)
Multiply equation 2 by 5/72:
{-(5 x) + 9 y = 12 | (equation 1)
0 x - y = 2 | (equation 2)
Multiply equation 2 by -1:
{-(5 x) + 9 y = 12 | (equation 1)
0 x+y = -2 | (equation 2)
Subtract 9 × (equation 2) from equation 1:
{-(5 x)+0 y = 30 | (equation 1)
0 x+y = -2 | (equation 2)
Divide equation 1 by -5:
{x+0 y = -6 | (equation 1)
0 x+y = -2 | (equation 2)
Collect results:
Answer: {x = -6 , y = -2